Reconstruction of Maqāṣid al-Syarī‘ah fī Ḥifẓ al-Māl in Responding to Doom Spending Among Generation Z and the Implications for Family Economic Resilience - Ubaidillah; Muhammad Yunus; Anita Mauliyanti; Asriadi; Bachrul Ulum; Mahmood Kooria (Al-Muamalat, 2026)
Generation Z increasingly engage in doom spending driven by global economic uncertainty, diminished confidence in long-term financial security, and the pervasive influence of digital consumer culture. This behavior undermines individual financial stability and threatens family and societal economic resilience. The rising prevalence of doom spending among Generation Z has become a significant concern, particularly regarding family economic resilience. Consequently, this study reconstructs Maqāṣid al-Syarī‘ah fī Ḥifẓ al-Māl as a normative and ethical framework to address impulsive, emotion-based consumption among Generation Z couples in the digital economy. Integrating Islamic ethics, psychological coping theory, and contemporary consumption studies, this research employs a qualitative method with descriptive-analytical design. Findings indicate that doom spending negatively impacts family financial stability, exacerbates emotional stress, and conflicts with core Islamic principles including moderation (wasaṭiyyah), contentment (qanā‘ah), and prohibition of extravagance (tabżīr). The study underscores strengthening family economic resilience through digital financial literacy, open financial communication between couples, integration of Islamic consumption values, productive technology utilization, and community-based financial education. By implementing these strategies, Generation Z couples can achieve balanced financial management, enhance household resilience, and align consumption behavior with ethical and spiritual principles. This research contributes to the broader discourse on integrating Islamic value-based approaches into contemporary financial practices and offers a conceptual framework for sustainable, morally responsible household economic management.